The espostoi pseudomeloe - Escomel, Edmundo (1919)
Peru is a country particularly well stocked Pseudomeloes, as found in vast tracts of its territory, and in the most diverse climates. Dr. ANGEL MALOONAOO has recently sent us some samples of Cockaigne i Huancayo poseeen very different characters all known species, and identical copies also sent us the doctor i Chuquibamba the ladies ALARCON, demonstrating that this species exists in a large extent of country. Well we understand that your location with new collections have to cover larger areas of Peru.